A new species of the genus Colilodion Besuchet, 1991 (Coleoptera: Staphylinidae: Pselaphinae) from Mindanao, the Philippines - Hlaváč, Peter; Vondráček, Dominik; Mohagan, Alma B. (Zootaxa, 2018)
Colilodion colongi sp. nov. of the clavigerite ant-loving beetle from Mindanao, the Philippines is described, illustrated, and distinguished from related species. The distribution map for all known species is given.